Sistem Pendukung Keputusan untuk Penentuan Jurusan dengan Metode Simple Additive Weighting (SAW) dan Pembobotan ROC - Jhiro Faran; Rima Tamara Aldisa (STMIK Budi Darma, 2023)
When someone chooses a major, they will focus on a particular area of study throughout their learning period. Usually, each department has a curriculum that has been specially prepared to provide in-depth understanding, specific skills and knowledge in that discipline. Decisions in choosing a major are often based on personal interests, talents, environmental influences, including parental views and personal career goals. Some courses may have specific entry requirements or may involve developing specific skills over the course of your studies. Apart from that, choosing a major can also influence the direction and career you will follow after graduating. Therefore, it is very important to make careful decisions and obtain the views of educational advisors or career counselors according to personal educational and career goals. This research discusses studies at a high school, where there are only two major choices, namely science and social studies. In the process of selecting majors, schools use special selection methods other than the general test route. The problem that arises is the need for flexibility and accuracy in decision making. To overcome this problem, researchers used a decision support system method by combining the ROC and SAW methods. ROC is used to calculate criteria weights, while SAW is used to assess preferences. The results of applying these two methods show that the initial major choices made by students are often different from the majors determined using these two methods. A total of five students were assigned to major in science, including alternatives A2, A3, A7, A8 and A10, while five other students were assigned to major in social sciences, namely alternatives A1, A4, A5, A6 and A9.